Controlled Formation of Patchy Anisometric Fumed Silica Supraparticles in Droplets on Bent Superhydrophobic Surfaces. (10th November 2016) - Sperling, Marcel; Spiering, Vivian J.; Velev, Orlin D.; Gradzielski, Michael
Abstract : This article presents a study on the formation of anisometric, ellipsoidal supraparticles by evaporation‐induced self‐assembly from multicomponent colloidal dispersion droplets deposited on a superhydrophobic surface. Performing the formation process on bent surface substrates grants precise control on the shape and spatial orientation of the final dried supraparticles. Due to the V‐shaped surfaces providing interfacial blockage, anisotropic evaporation rates occur with respect to the direction of the bending channel. This proportionally leads to inhomogeneous accumulation of fumed silica (FS), used as structure guiding component. Thus, upon the increase of FS‐particle interaction via ionic strength (NaCl), this so‐formed shell provides enough anisotropic stiffness resulting in predictable droplet deformation with the elongation orientation being perpendicular to the bending axis. The anisotropic evaporation rates were monitored and quantified using an established, empiric kinetic model and taking into account surface geometry. Employing this reliable control of elongation direction and using additional Fe3 O4 @SiO2 core–shell nanoparticles, anisometric magnetic Janus supraparticles with defined patch position were prepared, which are not accessible on flat surfaces. The results can find application in the controlled, easy to scale up, nanofabrication process of patchy anisometric supraparticles. Abstract : Controlled formation of anisometric supraparticles is achieved via drying of colloidal suspension droplets on bent superhydrophobic surfaces. Being inhomogeneously accumulated at the water–air interface during an anisotropic evaporation process, the contained fumed silica promotes droplet deformation with predictable orientation. Using Fe3 O4 @SiO2 nanoparticles under magnetic field influence allows to position the patches precisely with respect to the principal axes of the anisometric supraparticles.